Experiences, outcomes and unmet needs of caregivers of children with Cerebral Palsy in Spain: Protocol for a mixed-methods study - Clàudia Arumí-Trujillo; Francisco José Verdejo-Amengual; Oriol Martínez-Navarro; Jord J.T. Vink; Fran Valenzuela-Pascual (PLoS ONE, 2026)
Cerebral Palsy is one of the most prevalent motor disabilities in childhood, significantly impacting both children and their caregivers. This mixed-methods study explores the experiences, psychological well-being, and unmet needs of caregivers of children with Cerebral Palsy. Using an explanatory sequential design (QUAN → QUAL), first it will be assessed burden, stress levels, and quality of life of caregivers through standardized questionnaires (PedsQL-FIM, ZBI, PSS-14). In the second phase, semi-structured interviews will be conducted to provide a deeper understanding of these variables. Other studies indicate that caregivers experience heightened stress and decreased quality of life, influenced by their child’s functional limitations and the lack of adequate social and healthcare support. Moreover, many caregivers struggle with navigating medical systems, balancing personal and professional responsibilities, and managing emotional distress. This study will highlight the urgent need for family-centered interventions, psychosocial support, and healthcare policies that address not only the medical needs of children with Cerebral Palsy but also the well-being of their caregivers. By integrating quantitative and qualitative data, this research will provide comprehensive insights into the caregiving burden and will offer recommendations for improving caregiver support strategies. The Clinical Trial is registered at ClinicalTrials.org with the registration number NCT06912373.